Frozen elephant trunk versus conventional proximal repair of acute aortic dissection type I - Göbel, Nora; Holder, Simone; Hüther, Franziska; Anguelov, Yasemin; Bail, Dorothee; Franke, Ulrich (Frontiers in Cardiovascular Medicine, 2024)
The extent of surgery and the role of the frozen elephant trunk (FET) for surgical repair of acute aortic dissection type I is still under debate. Aim of the study is to evaluate the shortand long-term results of acute surgical repair of aortic dissection type I using the FET compared to standard proximal aortic repair.Between Oct 2009 and Dec 2016 a total of 172 patients underwent emergent surgery for acute type I aortic dissection at our center. Of these, n= 72 received a FET procedure, the other 100 patients had conventional proximal aortic repair. Results were compared according to type of surgery group. Primary endpoints were: 30-day rates of mortality and neurologic deficit, and follow-up rates of mortality and aortic-related reintervention.Demographic data were comparable between the groups except more men in the FET group (76.4% vs. 60.0%, p=0.03), median age was 62 years (IQR [20], p=0.17), and median log. EuroSCORE 38.6% (IQR [31.4], p=0.21). Mean follow-up time was 68.3 ± 33.8 months.Neither early (FET-group 15.3% vs. proximal-group 23.0%, p=0.25) nor late (FET-group 26.2% vs. proximal-group 23.0%, p=0.69) mortality showed significant differences between the groups. There were less strokes in the FET patients (FET-group 2.8% vs. proximal-group 11.0%, p=0.04), the rates of spinal cord injury were similar between the groups (FET-group 4.2% vs. proximal-group 2.0%, p=0.41). Aortic-related reintervention rates did not differ between the groups (FET-group 12.1% vs. proximal-group 9.8%, p=0.77).Emergent FET repair of acute aortic dissection type I is safe and feasible in experienced hands. The benefits of the FET procedure in the long-term remain unclear. Prolonged followup data are needed.